The effects of cue distinctiveness on odor-based context-dependent memory - Herz, Rachel S. (Memory & cognition, 1997)
The distinctiveness of an ambient odor was examined in relation to its success as a cue in context-dependent memory. Distinctiveness was examined in terms of both cue novelty and contextual appropriateness. Two experiments were conducted in which three different ambient odors that varied in familiarity and contextual appropriateness were manipulated at an incidental word learning encoding session and at a free recall retrieval session 48 h later. Experiment 1 revealed that when a novel ambient odor (osmanthus) was the available context cue, word recall was better than in any other condition. Further, among familiar odor cues, recall was better with a contextually inappropriate odor (peppermint) than with a contextually appropriate odor (clean fresh pine). Experiment 2 confirmed that superior word recall with osmanthus and peppermint depended on the odor cue's being available at both encoding and retrieval, and that the relation of an odor to the situational context is a key factor for predicting its effectiveness as a retrieval cue.